Design of three multibranch microstrip antennas compatible with WiMAX/WiFi/4G/5G NR for coal mine applications. Issue 3 (8th December 2022) - Xu, Yanhong; Zhang, Zhiwen; Wang, Anyi; Hou, Jianqiang
Abstract: In this letter, three microstrip antennas are designed and fabricated for coal mine applications, each of which can be compatible with WiMAX, WiFi, 4G, and 5G NR bands. The first one is the Pentagon antenna, which is realized by optimizing the sizes and positions of five branches. The second one is designed by adding a passive inverted L‐shaped branch on the top of a trident antenna. And the third one is designed by loading an inverted L‐shaped structure in the ground of the trident antenna. The simulated and measured results showed that each of the three proposed antennas can cover the frequency bands of 2.51–2.68, 3.40–3.60, and 4.80–4.90 GHz for commercial 5G NR of coal mines, 1.88–2.66 GHz for China Mobile/Unicom/Telecom full‐band of 4G, 2.40–2.484 GHz for WiFi, and 2.50–2.69 GHz for WiMAX. Good agreements between the simulated and measured results confirm the practical feasibility of the proposed multiband antennas.